Analisis Efektivitas Pelaksanaan E Government di Tingkat Kelurahan - Endah Mustika Ramdani (Sawala : Jurnal Administrasi Negara, 2018)
This study aims to analyze the practice of the implementation of e-government at the kelurahan level as the lowest level of governance. This study employed the descriptive qualitative method. Besides that, the search through various official documents record, in print and electronic mass media was also conducted. The results of the study showed that the level of e-government at the kelurahan level has not run effectively due to the lack of optimal infrastructure provision, efficiency, community satisfaction, apparatus adaptation to application, development, and lifespan. With technology, the government is able to use innovative ways of communicating with communities, these facilities can ideally improve the quality of government services and provide greater opportunities for the public participation in public service processes to support smartcity. Therefore, there must be efforts to improve such obstacles which can be done by improving infrastructure, developing human resource and strengthening regulations.